2021
DOI: 10.1515/biol-2021-0051
|View full text |Cite
|
Sign up to set email alerts
|

Gamma irradiation-mediated inactivation of enveloped viruses with conservation of genome integrity: Potential application for SARS-CoV-2 inactivated vaccine development

Abstract: Radiation inactivation of enveloped viruses occurs as the result of damages at the molecular level of their genome. The rapidly emerging and ongoing coronavirus disease 2019 (COVID-19) pneumonia pandemic prompted by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is now a global health crisis and an economic devastation. The readiness of an active and safe vaccine against the COVID-19 has become a race against time in this unqualified global panic caused by this pandemic. In this review, which we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 141 publications
0
8
0
2
Order By: Relevance
“…There are multiple methods for virus inactivation; however, common methods, such as chemical and heat inactivation, can damage structural proteins and viral antigens. 37 In contrast, γ‐irradiation can effectively inactivate a range of viruses 38 including SARS‐CoV‐2 39 whilst maintaining immunoreactivity. 40 The potent γ‐irradiated SARS‐CoV‐2‐induced activation of immune cells from SARS‐CoV‐2‐naïve adults in our assays supports the potential of γ‐irradiated SARS‐CoV‐2 vaccines 41 , 42 and provides a model for future studies assessing modulation of immune responses to SARS‐CoV‐2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are multiple methods for virus inactivation; however, common methods, such as chemical and heat inactivation, can damage structural proteins and viral antigens. 37 In contrast, γ‐irradiation can effectively inactivate a range of viruses 38 including SARS‐CoV‐2 39 whilst maintaining immunoreactivity. 40 The potent γ‐irradiated SARS‐CoV‐2‐induced activation of immune cells from SARS‐CoV‐2‐naïve adults in our assays supports the potential of γ‐irradiated SARS‐CoV‐2 vaccines 41 , 42 and provides a model for future studies assessing modulation of immune responses to SARS‐CoV‐2.…”
Section: Discussionmentioning
confidence: 99%
“…The development of this model for in vitro stimulation using inactivated virus enables analyses of immune responses to SARS‐CoV‐2 in a diverse range of laboratory settings. There are multiple methods for virus inactivation; however, common methods, such as chemical and heat inactivation, can damage structural proteins and viral antigens 37 . In contrast, γ‐irradiation can effectively inactivate a range of viruses 38 including SARS‐CoV‐2 39 whilst maintaining immunoreactivity 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Visualization of inactivated viral particles by TEM imaging suggested that formalin treatment affected more than γ-irradiation of the viral structure by reducing the height of surface immunogenic glycoproteins and by causing a more clustered appearance of H9N2 envelope projections, probably as a result of the cross-linking effect of the formalin treatment (46). The superiority of γ-irradiation to other chemical inactivation methods in the preservation of antigenic structures has been previously demonstrated and is due to the selective damaging effect of irradiation on the RNA genetic material, and the limited impact that irradiation has on proteins if frozen conditions are maintained during the inactivation process (47)(48)(49). In our work, to minimize the deleterious effects of γ-irradiation, we also used trehalose as a radio-protectant to preserve the antigenic epitopes during the irradiation process.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the current worldwide COVID-19 pandemic, many researchers have analyzed the efficiency of gamma radiation in inactivating this virus. Gamma radiation has been reported to play an important role in vaccine preparation via viral inactivation, as it has already shown potential inactivation efficacy against other enveloped viruses [59] . In addition, specimens of two other members of the COVID family, CoV-1 and CoV-2, are inactivated by gamma irradiation [60] , [61] .…”
Section: Methods For Viral Deactivationmentioning
confidence: 99%